2015
DOI: 10.1113/jp270463
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced changes in tumour LDH‐B and MCT1 expression are modulated by oestrogen‐related receptor alpha in breast cancer‐bearing BALB/c mice

Abstract: Key pointsr Monocarboxylate transporters (MCTs) and lactate dehydrogenase A (LDH-A) play important roles in sustaining the glycolytic phenotype seen in cancer.r Endurance training improves aerobic capacity; however, whether endurance training alters the metabolic phenotype of a solid tumour, from the perspective of lactate metabolism, is yet to be proven.r This study showed that endurance training decreases expression of the MCT1 basigin (CD147) and LDH-A , and also increases LDH-B expression in solid tumours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 58 publications
3
28
0
2
Order By: Relevance
“…Aerobic exercise normalizes the immunosuppressive, acidic tumor microenvironment. Treadmill running in mice with mammary carcinomas reduced tumor and circulating lactate concentrations by approximately 17% compared with sedentary counterparts (108). In sarcoma bearing rats (109), treadmill running decreased glucose conversion to lactate by approximately 50% in peripheral macrophages and lymphocytes.…”
Section: Exercise and Tumor Lactate/aciditymentioning
confidence: 92%
“…Aerobic exercise normalizes the immunosuppressive, acidic tumor microenvironment. Treadmill running in mice with mammary carcinomas reduced tumor and circulating lactate concentrations by approximately 17% compared with sedentary counterparts (108). In sarcoma bearing rats (109), treadmill running decreased glucose conversion to lactate by approximately 50% in peripheral macrophages and lymphocytes.…”
Section: Exercise and Tumor Lactate/aciditymentioning
confidence: 92%
“…Hypophysectomized rats, with reduced endogenous testosterone levels, showed increased testicular MCT2 mRNA expression that was reversed with testosterone treatment ex vivo (10). Inhibition of estrogen related receptor alpha decreased MCT1 expression in MC4-L2 human breast cancer -bearing BALB/c mice indicating that estrogen may be involved in MCT1 regulation (11) These data suggest that MCTs are regulated by sex hormones in a tissuespecific manner; however, there is a lack of information in the literature evaluating the role of sex hormones on MCT expression in tissues involved in drug disposition.…”
Section: Introductionmentioning
confidence: 95%
“…Eight prevention studies (40%) reported significant effects of exercise in modulation of local immune response, tumor metabolism and tumor physiology/angiogenesis. Ten progression studies (38.5%) examined mechanisms underlying the effects of exercise on tumor progression (32, 41, 42, 44, 52, 55, 57, 61, 68, 69). The mechanisms examined included multiple different factors/pathways such as apoptosis, perfusion and immune cell infiltration.…”
Section: Resultsmentioning
confidence: 99%